2013
DOI: 10.26530/oapen_627788
|View full text |Cite
|
Sign up to set email alerts
|

Soundscapes of the Urban Past : Staged Sound as Mediated Cultural Heritage

Abstract: An electronic version of this book is freely available, thanks to the support of libraries working with Knowledge Unlatched. KU is a collaborative initiative designed to make high quality books Open Access for the public good. This work is licensed under the Creative Commons Attribution-NonCommercial-NoDerivs 3.0 (BY-NC-ND). Creative Commons Attribution-NonCommercial-NoDerivs 3.0 (BY-NC-ND).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
1
15
0
2
Order By: Relevance
“…Among others, related services or cultural activities (tomorrow's heritage) include tourist promotion and environmental preservation/awareness for landscapes and intangible artifacts [1][2][3], sites modeling/reconstruction and content restoration/documentation [4,5], and multi-disciplinary collaborations in research and education innovations [6][7][8][9]. Audiovisual and soundscape-related heritage initiatives also emerge, focusing on historical sound records and landscapes preserved, re-created, and reproduced as means of intangible CH expressions [25][26][27][28][29]. Furthermore, the impact of environmental sounds, noise, and soundscape components is analyzed on various aspects of modern human life, i.e., examining their associations with the residents' physical/mental health, perception, and behavior, aiming to unveil factors of sustainable growth and development and overall quality of life as well [30][31][32][33][34][35][36][37].…”
Section: Related Workmentioning
confidence: 99%
“…Among others, related services or cultural activities (tomorrow's heritage) include tourist promotion and environmental preservation/awareness for landscapes and intangible artifacts [1][2][3], sites modeling/reconstruction and content restoration/documentation [4,5], and multi-disciplinary collaborations in research and education innovations [6][7][8][9]. Audiovisual and soundscape-related heritage initiatives also emerge, focusing on historical sound records and landscapes preserved, re-created, and reproduced as means of intangible CH expressions [25][26][27][28][29]. Furthermore, the impact of environmental sounds, noise, and soundscape components is analyzed on various aspects of modern human life, i.e., examining their associations with the residents' physical/mental health, perception, and behavior, aiming to unveil factors of sustainable growth and development and overall quality of life as well [30][31][32][33][34][35][36][37].…”
Section: Related Workmentioning
confidence: 99%
“…Feld (2012) has shown how certain forest populations knew (particularly well) how to listen to the world. At the crossroads of Sound Studies and Sciences and Technology Studies, Bijsterveld (2008 and 2013) has proposed a socio-history of noises (and therefore to a certain extent of pollution) and their social meanings.…”
Section: (Re)thinking Popular Music In the Anthropocene Eramentioning
confidence: 99%
“…In many ways, this situation merely reflects an ongoing problem faced by sound art as a whole: while it has for some years been gaining increasing recognition in the gallery-based art world, academia has been slow to follow this trend, with the established disciplines of both art history and musicology largely failing to engage with it. This has led to the gradual emergence of sound arts as an independent field of study, with its own growing body of critical scholarship; and within this can be found a number of texts which do engage with the links between the environment, environmental sound and sound art (Truax 2001; LaBelle 2006; Bandt, Duffy and MacKinnon 2007; Carlyle 2007; Rudi 2011; Bijsterveld 2013; Belgiojoso 2014; Gandy and Nilsen 2014). However, in these texts such issues are invariably viewed through the lens of acoustic ecology; and while many of its core principles are of undeniable importance to ecological sound art, the fundamental fact that acoustic ecology is by definition a field concerned with the acoustic environment means that it only tends to engage with contemporary environmental issues to the extent that they impact the environmental soundscape .…”
Section: The Absence Of Ecological Sound Art From Current Critical DImentioning
confidence: 99%